PERBEDAAN JUMLAH TRAY DENGAN METODE MULTIPLE TRAY ARERATOR PIRAMIDA TERHADAP PENURUNAN MANGAN AIR BERSIH PT. X - Bambang Purnama, Lubis; Muhammad Faudzan, Wishas; Nurhayati, Ati (Jurnal Sanitasi Profesional Indonesia, 2023)
Clean water PT.  Adetex Filaments are sourced from surface water.  Manganese (Mn) levels in clean water at PT.  Adetex Filament after inspection is 1.10 mg/L and exceeds the quality standard, it is necessary to carry out an aeration process using the multiple tray aerator method.  The purpose of this study was to reduce levels of Manganese (Mn) in clean water and to determine the difference in the effect of the number of trays on the aeration process with the multiple tray aerator method with 3 trays, 5 trays, and 7 trays.  This type of research is experimental research design with pretest-posttest without control.  The population in this study is all clean water used in PT.  Adetex Filament.  Some of the clean water is taken from the population, the sampling technique is grab sampling, the data collection technique is by checking Mn, pH and temperature.  Nivatiat analysis and bivariate analysis with One-Way Anova test and Posh Hoc test.  The average initial Mn content in clean water is 1.12 mg/L.  The average level of Mn in clean water after the aeration process with 3 trays is 0.83 mg/L with a percentage decrease of 23.8%, 5 trays 0.62 mg/L with a percentage decrease of 44.4% and  7 trays that is 0.22 mg/L with a percentage decrease of 79.7%.  The test carried out in this study is the One-Way Anova test with the results of the statistical test, namely p.  value 0.002 < 0.05 so that there are differences in the number of trays in the aeration process with the multiple tray aerator method on the decrease in Mn levels.